Decay of a massive particle in a stiff-matter-dominated universe - Lankinen J; Vilja I (AMER PHYSICAL SOC, 2022)
In the presence of a gravitational field, decay rates may significantly differ from the flat space equivalent. By studying mutually interacting quantum fields, the decay rates can be calculated on a given spacetime. This paper presents the calculation of the transition probability for the decay of a massive scalar particle in a stiff-matter-dominated universe. We find that, due to the presence of a gravitational field, a finite correction to the transition probability is added which depends inversely on the mass. Moreover, the decay rate is smaller, and lifetime of the particles is longer compared to flat space. The mass dependence is such that the lifetime of lighter particles is prolonged more compared to heavier particles. This result may be of significance when studying cosmological situations involving stiff matter.